(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
Each time less considered a fad the knowledge management (KM), as more present in the organizations. Some definitions of the KM point out the technological solutions through the concept turned to the knowledge storing others value the human element due to the knowledge sharing. The goal of this research was to raise similar characteristics in the way the organization have worked the KM, supported the research presented at the Encontro Nacional de Pesquisa e Pós-Graduação em Ciência da Informação (ENANCIB), considered an "enabling framework", fitting them to two possibilities of management: people and technology. The research is characterized in relation to the design, as exploratory and descriptive study, and in relation to the nature as research of qualitative and quantitative approaching been defined as a kind of bibliographic and field study, with the intention to analyze the scientific production about KM. They were defined like variable, the characterization of the articles published in the ENANCIB in the period 2008/2009, about the insertion of the KM in the WG-4, the evolution of the KM in the WGs, the role of the people in the KM and the role of the IT tools applied to the KM. The results permitted to conclude that the KM has been spreading in a testimonial way, not only in the corridors of the organizations but also in the “enabling context” promoted by the managers and researchers who produce the ENANCIB, adopting as central and defining characteristic – the human capital – and his interfaces with the IT and the Information Science (IS). link para o texto completo: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/348/395